Relación del consumo de alimentos de bajo nivel nutricional con la obesidad estudiantil en la Escuela Jorge Icaza cuidad Latacunga - Soria Coro, Gabriela Izamar (2015)
The present investigative work is aimed at “Being aware of the adequate consumption of nutritive food, by means of a design of an educative video to prevent student obesity in the children of the Jorge Icaza School”. The problem to be investigated was how does the consumption of low-nutritional food influence in children obesity, at the Jorge Icaza School in Latacunga city? The methodology corresponds to the quantitative modality since it uses statistics in the processing of information; also the descriptive method it specified the characteristics of the study target, bibliographic; because printed documents were searched, and field investigation since surveys were applied in the place of the scene. The conclusions of this research were: students have some food problem, such as malnutrition and obesity, a factor that incidence in discrimination, effecting academic performance and self-esteem. The contribution of this thesis is the edition of an educative video for the improvement of life quality in all the educative community